A rare case of imatinib-induced erythroderma - Verma, Rajesh (Medknow Publications & Media Pvt Ltd, 2013)
Imatinib, a specific tyrosine kinase inhibitor is a newer anticancer agent, which has shown excellent efficacy in managing chronic myeloid leukemia. It is generally well tolerated with few side effects. Most commonly reported adverse events are maculopapular eruptions and periorbital edema. Severe adverse reactions are seen in 5% of patients. Exfoliative dermatitis has been very rarely reported with this drug. We report a case of a 52-year-old male who initially presented with a maculopapular rash and developed erythroderma on continuation of the drug.